The Autonomous Self: A Way to Go With Overcoming Limitations in English Learning - Edson Estarneck (Studies in Self-Access Learning Journal)
When students first enter the Teaching English and Portuguese Program at a private university in Rio de Janeiro, some of them struggle with their English literacy. However, despite these initial difficulties, some students persist and successfully graduate. This study examines the role of the autonomous self in this process, and how it is shaped by the learner’s experiences in the learning process. The research is based on sociocultural theories and uses narrative inquiries and Complexity Theories as methodological foundations. The research question aims to understand what allows some students to overcome their initial language barriers and remain in the program, while others tend to drop out. The results show that the autonomous self acts as a motivator and a learner’s potential, becoming a crucial factor in their success.